Online Disposition Data Based Management System - Septian Rheno Widianto; Maria Magdalena (Jurnal Mantik, 2020)
The development of technology nowadays is so fast, technology has become part of the people's lifestyle. The presence of technology in human life can facilitate and accelerate all activities carried out so as to increase work effectiveness. Including services via smartphones and the internet. This has prompted many companies to develop their network and technological facilities. To be able to continue to develop in this increasingly rapid technological era, a company needs to present a data management system, namely a database system that provides computerized services and facilities. The main principle of a database system is to organize a set of interrelated data, while the main purpose of a database is the ease and speed of retrieving data to solve problems in systems that use a file-based approach. The result of this research is to observe the online disposition system data management.